Poster Presentations 2018
DOI: 10.1136/bmjspcare-2018-aspabstracts.140
|View full text |Cite
|
Sign up to set email alerts
|

113 The swinburne slot: a clinic-based service for deteriorating patients with interstitial lung disease

Abstract: Methodology Using Shropshire Doctors Co-operative Ltd (Shropdoc's) recorded data we have collated a representative picture of the palliative care practice over a year period from 161 OOHGP patient interactions. Results 31% of home visits (HV) had documentation of potential reversible factors and out of those 72% were with the patient's estimated prognosis greater than 48 hours. Infection being the most common (57%) reversible factor, the majority being a lower respiratory tract infection. Overall 5.7% of OOH G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A novel rapid clinic review pathway was developed in the UK by Newcastle-upon-Tyne Hospitals interstitial lung disease service for patients who required urgent ad-hoc review. 68 Patients were reviewed urgently in the clinic and were referred for appropriate investigations, started on treatment for intercurrent illness and many were also reviewed by palliative care services on the same day. Feedback from this service indicated that patients and their carers felt supported as they were able to be reviewed by the interstitial lung disease specialists quickly, which avoided delays which may have been fostered by repeated visits in primary care.…”
Section: What Our Study Addsmentioning
confidence: 99%
“…A novel rapid clinic review pathway was developed in the UK by Newcastle-upon-Tyne Hospitals interstitial lung disease service for patients who required urgent ad-hoc review. 68 Patients were reviewed urgently in the clinic and were referred for appropriate investigations, started on treatment for intercurrent illness and many were also reviewed by palliative care services on the same day. Feedback from this service indicated that patients and their carers felt supported as they were able to be reviewed by the interstitial lung disease specialists quickly, which avoided delays which may have been fostered by repeated visits in primary care.…”
Section: What Our Study Addsmentioning
confidence: 99%